Design an operational amplifier for neutro chemical sensor: article - Wan Kamaruddin, Wan Mohd Fahmi; Kassim, Jamilah (2009)
This project needs to design an operational amplifier (op-amp) for neutron chemical sensor. The op-amp is amplifying the input current in nanoampere (-800nA to 800nA) and converts the signal into voltage. This low power amplifier designed with high gain and high sensitivity because output current from neutron chemical sensor very small. The designed consists combination of current amplifier, differential amplifier, voltage amplifier, class AB power amplifier and high sensitivity current-to-voltage converter. The low power amplifier output should capable to drive the voltage-to-frequency converter (VFC). This op-amp is a part of the main project the wireless voltammetry recording in unaesthetized behaving rats. Vivo voltammetry is a valuable technique for rapid measurement of dopamine in the brain of freely behaving rats. Using a conventional voltammetry system, however, behavioral freedom is restricted by cables connecting the head assembly to the measurement system. This system consisted of a potentiostat and transmitter system activation pulse to a carbon fiber recording electrode where the process would produce the signal and then the op-amp converts the signal into voltage before convert the signal into frequency by VFC. The Multisim8 design tool software is used to design and simulate the op-amp circuit.